The early Cambrian tommotiid Kulparina rostrata from South Australia. (9th May 2016) - Skovsted, Christian B.; Brock, Glenn A.; Holmer, Lars E.; Topper, Timothy P.; Larsson, Cecilia M.
Abstract: The early Cambrian (Terreneuvian, Stage 2) tommotiid Kulparina rostrata Conway Morris and Bengtson in Bengtson et al., 1990 is revised. The pyramidal sclerites of K. rostrata are shown to be bilaterally symmetrical and homologues of the symmetrical S1 sclerites of Paterimitra pyramidalis Laurie, 1986 . The scleritome of K. rostrata is also shown to include flattened asymmetrical sclerites that were originally described under the name Eccentrotheca guano Bengtson in Bengtson et al., 1990 and which correspond to the L-sclerites of Paterimitra . A modified tubular scleritome and a sessile filter-feeding mode of life is envisaged for Kulparina rostrata .